Penyelesaian Permasalahan Akta Kelahiran yang Cacat Yuridis dan Tidak Mempunyai Kekuatan Hukum Mengikat: (Putusan Mahkamah Agung Nomor 2438 K/PDT/2019 Kabupaten Tulungagung) - Marven A. Kasenda; Disya Modeong; Wa Rina; Febrianty S. Tamasoleng; Muhammad Furqhon; Brigitha Wilda; Rifaldi Mamonto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to identify the causes behind the issuance of legally defective and non-binding birth certificates in Tulungagung Regency based on Supreme Court Decision No. 2438 K/Pdt/2019, and their legal impact on individuals. The research method used is normative juridical with a case study approach. The findings reveal that administrative errors and verification negligence are the main causes, affecting access to civil rights such as education and legal protection. The discussion highlights the urgency of improving the civil registration system to protect citizens' legal rights.